REFLEKSI NILAI SEGARA KERTHI DALAM GAME SEGARA WATCH SEBAGAI MEDIA EDUKASI - I Wayan Suwadnyana; Saskara, I Putu Adi; Bagus Nesa Sanjaya (Guna Widya: Jurnal Pendidikan Hindu, 2024)
The development of information and communication technology has opened the door to various educational innovations, and one of the innovations that stands out is the use of video games as an educational medium. In this context, the game "Segara Watch" has emerged as an educational tool that attracts attention. "Segara Watch's" innovative approach in combining technology with Balinese culture as an educational medium offers great potential in enriching education and preserving cultural heritage. Therefore, this research aims to explore how the values of Segara Kerthi are reflected in the game "Segara Watch" and to analyze its impact as an educational tool as well as introducing and promoting Balinese cultural values, especially Segara Kerthi, to the players. This research was analyzed using symbolic communication theory. Using interview, survey and observation collection methods to understand how this game influences their understanding of Balinese cultural values, especially the concept of Segara Kerthi. The results of this research have important significance. First, this research will provide deeper insight into the role of video games as an educational tool rich in cultural values. Second, this research will provide an understanding of how prospective young people, parents, teachers and the community respond to the Segara Watch game and how this game helps promote and preserve Balinese cultural values related to the Segara Kerthi concept.